Gambaran Ketersediaan Rekam Medis Rawat Jalan Berdasarkan Standar Pelayanan Minimal di Rumah Sakit Islam Jakarta Pondok Kopi - Paryati Paryati; Deasy Rosmala Dewi; Daniel Happy Putra; Nanda Aula Rumana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The availability of medical records is greatly influenced by fast and precise distribution. If the delivery of medical records to the intended polyclinic is not on time, it will affect the waiting time for patient services. The general objective of this study was to determine the length of time it took to provide outpatient medical records at RSIJ Pondok Kopi. This type of research uses descriptive, quantitative in nature, namely a survey conducted on a set of objects which usually aims to see a picture of what is happening in a certain population. From the results of research conducted in the medical record storage room, all procedures have been carried out properly. It's just that there is still a procedure that does not exist in this case, namely standardization of the time for providing medical records for outpatient services. Based on the conclusions that can be drawn from the results of the study, namely: in the implementation of taking and compiling medical records the officers carry out according to the SPO, it's just that there is no standardization of the length of time for providing medical records for outpatient services from the patient registering until the medical record is available / found. Some suggestions that can be useful for service providers are: it is hoped that there will be a standard time regarding the provision of medical records for outpatient services, so that officers can speed up the process of providing medical records.